1984
DOI: 10.1007/bf00262211
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymatic glycosylation of urinary proteins in Type 1 (insulin-dependent) diabetes: correlation with metabolic control and the degree of proteinuria

Abstract: In 18 control subjects and in 41 Type 1 (insulin-dependent) diabetic patients (13 with normal proteinuria, group A; 15 with microproteinuria, group B; and 13 with clinical proteinuria, group C), mean blood glucose, glycosylated haemoglobin and non-enzymatic glycosylated serum and urinary proteins, expressed as 5-hydroxymethylfurfural (5-HMF), were measured. In each group of diabetic patients, the levels of mean daily blood glucose, glycosylated haemoglobin and serum 5-HMF/mg protein were higher than in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 17 publications
0
2
2
Order By: Relevance
“…The increased selectivity index found in normoalbuminuric patients is hardly explained by increased tubular reabsorption of the more anionically charged glycated albumin, since an increased tubular reabsorption of cationic albumin has been demonstrated in rats [17]. Our results disagree with previous observations of a preferential urinary excretion of glycated protein in diabetic patients [19,20]. The method used by these authors for determination of glycated proteins was, however, less specific [5] and unreliable in our hands [6].…”
Section: Discussioncontrasting
confidence: 95%
“…The increased selectivity index found in normoalbuminuric patients is hardly explained by increased tubular reabsorption of the more anionically charged glycated albumin, since an increased tubular reabsorption of cationic albumin has been demonstrated in rats [17]. Our results disagree with previous observations of a preferential urinary excretion of glycated protein in diabetic patients [19,20]. The method used by these authors for determination of glycated proteins was, however, less specific [5] and unreliable in our hands [6].…”
Section: Discussioncontrasting
confidence: 95%
“…This finding indicates that in normoalbuminuric diabetic patients the renal excretion of glycated albumin is relatively lower than that of non-glycated albumin, as previously documented by Kverneland et al [7,8] on 24-h urine collection during normal physical activity. On the other hand, our results and those of Kverneland et al disagree with the preferential urinary excretion of glycated proteins reported by others [5,6] using a method considered as poorly specific for glycated albumin [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Administration of anti-glycated albumin antibody in animal models reduces plasma levels of glycated albumin, reduces AER, and reverses glomerular pathology (22). Human studies have been conflicting, perhaps in part because of small numbers and confounding by other risk factors, but one of the largest previous studies clearly indicated that Amadori albumin levels were elevated in individuals with nephropathy compared with individuals without nephropathy (15,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%